PERSONALITY-ORIENTED TEACHING OF PHYSICS (Pedagogy of Higher and Secondary Education, 2003)
On the base of тапу years' watching, analysis of advanced teaching experience and research-experimental work, the ways, conditions, approaches, varions forms and methods of work of effective personal-orientative studying ofphysics and its theoretical interprétation are shown.